2022
DOI: 10.3390/diagnostics12102454
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Models for the Prediction of Renal Failure in Chronic Kidney Disease: A Retrospective Cohort Study

Abstract: This study assessed the feasibility of five separate machine learning (ML) classifiers for predicting disease progression in patients with pre-dialysis chronic kidney disease (CKD). The study enrolled 858 patients with CKD treated at a veteran’s hospital in Taiwan. After classification into early and advanced stages, patient demographics and laboratory data were processed and used to predict progression to renal failure and important features for optimal prediction were identified. The random forest (RF) class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Recently, Mondol achieved high accuracy in early CKD prediction using convolutional neural network, ANN, and long short-term memory models [ 25 ]. In our recent study, high performance was obtained for predicting CKD progression using random forest methods, with C-indexes of 0.96 within 5 years in the early stage and 0.97 within 1 year in the advanced stage [ 14 ]. Although the models proposed by previous studies show high performance, the quality and accuracy of the estimates may vary over time [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, Mondol achieved high accuracy in early CKD prediction using convolutional neural network, ANN, and long short-term memory models [ 25 ]. In our recent study, high performance was obtained for predicting CKD progression using random forest methods, with C-indexes of 0.96 within 5 years in the early stage and 0.97 within 1 year in the advanced stage [ 14 ]. Although the models proposed by previous studies show high performance, the quality and accuracy of the estimates may vary over time [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our recent study, using the Shapley additive explanation value method, the urine creatinine and eGFR were the most and second-most important predictive features in patients diagnosed with advanced-stage CKD within 3 and 5 years. In addition, serum creatinine was the most important predictive feature in patients diagnosed with advanced-stage CKD within 1–3 years [ 14 ]. Ultimately, the key predictive features may help determine the optimal predictive models for the progression from CKD to ESRD.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study enrolled 858 patients with CKD and predicted progression to renal failure and important features, which revealed that a random forest (RF) classi er with a synthetic minority oversampling technique (SMOTE) had the best predictive performance among patients with early-stage CKD who progressed within 3 and 5 years and among patients with advanced-stage CKD who progressed within 1 and 3 years [23]. The RF algorithm also has many applications in other disease prediction models.…”
Section: Discussionmentioning
confidence: 99%